2018
DOI: 10.1007/s00210-018-1523-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of brain ACE and ACE2 may be a promising protective strategy against cerebral ischemia/reperfusion injury: an experimental trial in rats

Abstract: The brain renin-angiotensin system (RAS) is considered a crucial regulator for physiological homeostasis and disease progression. We evaluated the protective effects of the angiotensin receptor blocker (ARB) telmisartan and the angiotensin-converting enzyme 2 (ACE2) activator xanthenone on experimental cerebral ischemia/reperfusion (I/R) injury. Rats were divided into a sham control, a cerebral I/R control, a standard treatment (nimodipine, 10 mg/kg/day, 15 days, p.o.), three telmisartan treatments (1, 3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…It was also shown that ACE2 activation by XNT protected experimental pregnant rats against leptin induced hypertension and proteinuria [76] and reduced hypertension-induced cardiac fibrosis in SHR [77]. Moreover, it was also shown to increase brain tissue ACE2 gene expression in cerebral ischemia/reperfusion injury in experimental rats [78].…”
Section: Role Of the Alternate Ras In Hepatic Fibrogenesismentioning
confidence: 95%
“…It was also shown that ACE2 activation by XNT protected experimental pregnant rats against leptin induced hypertension and proteinuria [76] and reduced hypertension-induced cardiac fibrosis in SHR [77]. Moreover, it was also shown to increase brain tissue ACE2 gene expression in cerebral ischemia/reperfusion injury in experimental rats [78].…”
Section: Role Of the Alternate Ras In Hepatic Fibrogenesismentioning
confidence: 95%
“…First, preclinical studies were searched in the PubMed database, and all the related studies [ [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ] are listed in Table 1 . Kidoguchi et al [ 46 ] analyzed the expression of ACE2 in adenine-induced chronic renal failure model mice, and the results suggested that azilsartan did not increase ACE2 expression in the kidney compared to the control group.…”
Section: Raas Inhibitor Use and Ace2 Expressionmentioning
confidence: 99%
“… Source Animal Model Study design Effect of RAAS blockers on ACE2 Kidoguchi [ 46 ],2019 Mice Adenine-induced chronic renal failure model Azilsartan (ARB); 2 mg/kg/day orally for 4 weeks Compared to the vehicle group, azilsartan didn't increased ACE2 expression in kidney. Abdel-Fattah [ 47 ], 2018 Rat A cerebral ischemia/reperfusion (I/R) injury model Three telmisartan (ARB) treatments: 1, 3, and 10 mg/kg/day; orally for 15 days Telmisartan in the higher doses significantly increased ACE2 expression compared to I/R control values. Wang W [ 48 ], 2018 Mice A chronic intermittent hypoxia model Telmisartan (ARB); 10 mg/kg/d for 4 weeks, intragastrically Telmisartan elevated the expression of cardiac ACE2.…”
Section: Raas Inhibitor Use and Ace2 Expressionmentioning
confidence: 99%
“…ACE2 is a type 1 integral membrane protein that functions as an extracellular receptor attached to the plasma membrane of cells in the lungs, heart, brain, and other vital organs [ 14 , 15 ]. It is primarily expressed on type 2 pneumocytes in the lungs and on enterocytes in the small intestine.…”
Section: The War Against Covid-19mentioning
confidence: 99%